Pengalaman Remaja Hidup Bersama Ayah dengan Skizofrenia - Sarah Kusumah Bakti; Hana Rizmadewi Agustina; Aat Sriati (Jurnal Keperawatan Silampari, 2022)
This study aims to determine the experiences of adolescents who live with fathers with schizophrenia in adolescent life and development. The research method used is Scoping Review through electronic databases and websites, namely PsycINFO, EBSCO, Pubmed, and Google Scholer. The results showed that from 8 research articles, there were articles that reported that there was a change in roles, adolescents felt lonely and missed their father, the effect on future orientation, felt anxiety, stress, hypersensitivity, and decreased concentration, is a form of affection and respect for people. Adolescents get a lot of stigmas as they age, become more independent, and need support from family, friends, education, and health services. In conclusion, this study concludes that adolescents living with schizophrenic fathers affect the lives and development of adolescents, and the need for handling psychosocial problems for adolescents living with schizophrenic fathers must consider the psychological and social impacts of caring for fathers with schizophrenia. Keywords: Father, Parents, Experience, Adolescent, Schizophrenia